Preparation method of AgSnO2In2O3Bi2O3 electric contact material

By using oxidation treatment and multi-mode pressing of AgSnIn and AgSnBi alloy powders in silver-based electrical contact materials, the problems of limited material performance and low material yield in the prior art are solved, and the preparation of high-performance and low-cost silver-based electrical contact materials are realized.

CN120119137APending Publication Date: 2025-06-10WENZHOU HONGFENG ELECTRICAL ALLOY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510345652.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

The existing silver-based electrical contact material preparation technology has problems such as complex process, low production yield and limited material performance, including blank defects, processing losses, uneven oxidation, arc erosion and other problems.

Method used

The AgSnIn alloy powder and AgSnBi alloy powder were oxidized to form AgSnO2In2O3 and AgSnO2Bi2O3 powders, and the AgSnO2Bi2O3 electrical contact material was prepared through multi-mode pressing, continuous sintering and secondary molding pressing processes, combined with heat treatment.

Benefits of technology

It realizes a uniform multi-phase reinforcement structure of the material, improves the interface bond strength, density, and resistance to arc erosion, and significantly improves the production rate and material yield of electrical contacts, which is suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120119137A_ABST
    Figure CN120119137A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an AgSnO2In2O3Bi2O3 electric contact material. The preparation method comprises the following steps: providing AgSnIn alloy powder and AgSnBi alloy powder; the AgSnIn alloy powder and the AgSnBi alloy powder are subjected to oxidation treatment, and AgSnO2In2O3 powder and AgSnO2Bi2O3 powder are formed; the preparation method comprises the following steps: mixing AgSnO2In2O3 powder, AgSnO2Bi2O3 powder, an additive I and silver powder; performing multi-mold pressing; continuously sintering; carrying out secondary forming and pressing; and carrying out heat treatment to obtain the AgSnO2In2O3Bi2O3 electric contact material. According to the invention, ternary oxide composite reinforcement is adopted, and modes of secondary pressing and the like are combined, so that reinforcement phase segregation and reinforcement phase distribution uniformity are improved, and the interface bonding strength, the material density and the arc erosion resistance of the electric contact material are effectively improved; and the production efficiency of the electric contact material is effectively improved, the processing method is simple, and the yield is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrical contact materials, and in particular to an AgSnO 2 In 2 O 3 Bi 2 O 3 Method for preparing electrical contact material. Background Art

[0002] Silver-based electrical contact materials are core components responsible for conducting and breaking circuits in electrical and electronic products such as circuit breakers. Their performance directly affects the reliability, life and safety of electrical products. Currently, silver-based electrical contact materials widely used in the electrical field need to be added with metal oxides such as SnO 2 etc. to improve its mechanical strength, wear resistance and other properties. Silver tin oxide (AgSnO 2 ) is widely used in circuit breakers, contactors, relays and other fields because of its environmental protection, non-toxicity and pollution-free, excellent resistance to arc erosion, and good resistance to material transfer under DC load.

[0003] However, the existing preparation technology for preparing silver tin oxide electrical contact materials still faces bottleneck problems such as complex process, low production yield and limited material performance, which are specifically manifested as follows:

[0004] The existing extrusion method can improve the density of the material through hot extrusion molding, as described in the patents with publication numbers CN114360948A, CN107794389A, and CN101964260A, but due to the defects of the blank and the processing loss, the yield rate is low, the waste recycling is difficult, and the resource utilization rate is low;

[0005] In the existing alloy internal oxidation method, the material is prone to form an "oxide-poor zone" during the oxidation process. This area is prone to cause electrical contact bonding failure under repeated arc action, resulting in nearly 50% of the material thickness being unable to be effectively utilized. In addition, its oxidation cycle is long, production efficiency is low, energy consumption is high, and production costs are high.

[0006] The existing powder metallurgy methods include: mechanical powder mixing process and pre-oxidation process. In the mechanical powder mixing method, due to the poor wettability between the reinforcing phase and the matrix, problems such as oxide agglomeration and tissue coarsening are likely to occur, affecting the electrical conductivity and arc resistance performance; although the pre-oxidation process can refine the oxide distribution, the density of the sintered material is insufficient, and subsequent repressing processes are required to improve the performance. After the prepared electrical contact material undergoes multiple breakings, repeated arc erosion is likely to cause obvious segregation on the contact surface, seriously reducing the service life of the contact. Some researchers have tried to improve the deficiencies of these technologies. For example, the method described in Patent CN102328086A combines internal oxidation and powder metallurgy processes, improves the activity of the powder through hydrogen reduction treatment, shortens the oxidation time and eliminates the oxygen-depleted region. However, this method requires repressing and forming the green body under high temperature and high pressure, which is likely to cause internal stress concentration in the material and has strict requirements for the mold accuracy, restricting continuous production.

[0007] With the improvement of the performance requirements for electrical contact materials in high- and low-voltage electrical appliances and new energy equipment, it is urgent to develop a preparation method for electrical contact materials with a uniform multi-phase reinforcement structure and high-efficiency continuous production capacity. Summary of the Invention

[0008] Aiming at the defects in the prior art, the purpose of the present invention is to provide a preparation method for an AgSnO 2 In 2 O 3 Bi 2 O 3 electrical contact material to achieve large-scale preparation of environmentally friendly, low-cost and high-performance electrical contact materials.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] The present invention provides a preparation method for an AgSnO 2 In 2 O 3 Bi 2 O 3 electrical contact material, including:

[0011] Providing AgSnIn alloy powder and AgSnBi alloy powder;

[0012] Performing oxidation treatment on the AgSnIn alloy powder to form AgSnO 2 In 2 O 3 powder; performing oxidation treatment on the AgSnBi alloy powder to form AgSnO 2 Bi 2 O 3 powder;

[0013] Mixing the AgSnO 2 In2 O 3 powder, the AgSnO 2 Bi 2 O 3 powder, additive one and silver powder are mixed to obtain a mixed powder;

[0014] The mixed powder is multi-mode pressed to obtain AgSnO 2 In 2 O 3 Bi 2 O 3 green body;

[0015] The AgSnO 2 In 2 O 3 Bi 2 O 3 green body is continuously sintered to obtain a sintered green body;

[0016] The sintered green body is subjected to secondary forming pressing;

[0017] The green body after secondary forming pressing is heat-treated to obtain AgSnO 2 In 2 O 3 Bi 2 O 3 electrical contact material.

[0018] Optionally, the providing of AgSnIn alloy powder and AgSnBi alloy powder includes:

[0019] Using silver, tin, indium and additive two as raw materials, atomizing and powder making are carried out by any one of water atomization, gas atomization, supersonic gas atomization, rotating electrode atomization, ultrasonic atomization and plasma atomization, and screening through 100 - 400 meshes to obtain AgSnIn alloy powder;

[0020] Using silver, tin, bismuth and additive three as raw materials, atomizing and powder making are carried out by any one of water atomization, gas atomization, supersonic gas atomization, rotating electrode atomization, ultrasonic atomization and plasma atomization, and screening through 100 - 400 meshes to obtain AgSnBi alloy powder.

[0021] Optionally, the additive two is any one or more of Cu, Zn, Ni, Fe, Te and Ge; the additive three is any one or more of Cu, Zn, Ni, Fe, Te and Ge.

[0022] Optionally, in the step of oxidizing the AgSnIn alloy powder and / or oxidizing the AgSnBi alloy powder, the oxidation temperature is 400°C to 700°C, the oxidation time is 1 to 12 hours, and the atmosphere is air or an oxygen atmosphere.

[0023] Optionally, the AgSnO 2 In 2 O 3 powder, the AgSnO 2 Bi 2 O 3 powder, additive one, and silver powder are mixed to obtain a mixed powder, where: additive one is at least one of W and rare earth elements.

[0024] Optionally, before multi-mode pressing the mixed powder, it includes: wet ball milling the mixed powder.

[0025] Optionally, the mixed powder is multi-mode pressed to obtain an AgSnO 2 In 2 O 3 Bi 2 O 3 green body, including: laying silver powder at the bottom of each cavity of a forming die with multiple cavities in advance, then feeding the mixed powder into each cavity in the forming die, and subsequently performing in-die pressing to form, obtaining multiple AgSnO 2 In 2 O 3 Bi 2 O 3 green bodies.

[0026] Optionally, the AgSnO 2 In 2 O 3 Bi 2 O 3 green body is continuously sintered to obtain a sintered body, where: the sintering temperature is 600°C to 900°C, the sintering time is 1 hour to 10 hours, and the sintering atmosphere is any one of air, nitrogen, and inert gas.

[0027] Optionally, the sintered body is subjected to secondary forming pressing, where: the pressure of the secondary forming pressing is 600 MPa to 800 MPa, and the pressure holding time is 0.1 second to 60 seconds.

[0028] Optionally, the green body after secondary forming pressing is heat-treated to obtain an AgSnO 2 In 2 O 3 Bi 2 O 3The electrical contact material has a heat treatment temperature of 300° C. to 550° C. and a heat treatment time of 0.5 to 6 hours.

[0029] Compared with the prior art, the present invention has at least one of the following beneficial effects:

[0030] 1. In the method provided by the present invention, the multi-oxide is generated in situ, that is, AgSnIn is in situ oxidized to AgSnO 2 In 2 O 3 , AgSnBi is in situ oxidized to AgSnO 2 Bi 2 O 3 , so that the oxidized reinforcement phase powder contains Ag, thereby enhancing the interface bonding strength between the reinforcement phase and the silver matrix; by mixing multiple oxides and combining secondary pressing and other processes, the multiple reinforcement phase is fully mixed and evenly mixed, and at the same time a layer of pure silver is coated on the surface of the reinforcement phase, which solves the problems of conventional mechanical powder mixing methods that easily lead to interface segregation of multiple oxide composite reinforcements, uneven distribution of reinforcement phases, and weak bonding between the reinforcement phase and the matrix, thereby improving the product's interface bonding strength, material density and resistance to welding.

[0031] 2. AgSnO prepared by the present invention 2 In 2 O 3 Bi 2 O 3 The electrical contact material uses three oxides to enhance the performance of silver-based electrical contact materials. 2 Environmentally friendly and non-toxic, and excellent resistance to material transfer under DC load, while also taking into account In 2 O 3 The wettability improvement effect of Bi 2 O 3 The effect of improving the resistance to welding is significantly improved over conventional AgSnO 2 The coarse particles of the material reinforcement phase and the deterioration of the welding resistance caused by the material segregation can further improve the electrical performance and service life of the product.

[0032] 3. The present invention adopts multi-mode pressing and continuous sintering. Compared with the extrusion method, the present invention does not need to remove the head and tail of the material, has a high material utilization rate, and can process multiple blanks at a time, which significantly improves the production rate and yield rate of the electrical contacts and is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0034] Figure 1In an embodiment of the present invention, AgSnO 2 In 2 O 3 Bi 2 O 3 Schematic flow diagram of the preparation method of the electrical contact material;

[0035] Figure 2 Schematic structural diagram of the multi-mode cavity forming die in an embodiment of the present invention;

[0036] In the figure, the reference numerals correspond to: 1 - upper die, 2 - lower die, 3 - cavity, 4 - punch. Detailed implementation manners

[0037] The present invention will be described in detail below with reference to specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be noted that those of ordinary skill in the art can make several modifications and improvements without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0038] Refer to Figure 1 As shown, the preparation method of the AgSnO 2 In 2 O 3 Bi 2 O 3 electrical contact material provided by an embodiment of the present invention includes the following steps:

[0039] Step 1: Provide AgSnIn alloy powder and AgSnBi alloy powder;

[0040] Step 2: Oxidize the AgSnIn alloy powder to form AgSnO 2 In 2 O 3 powder; Oxidize the AgSnBi alloy powder to form AgSnO 2 Bi 2 O 3 powder;

[0041] Step 3: Mix the AgSnO 2 In 2 O 3 powder, AgSnO 2 Bi 2 O 3 powder, additive 1 and silver powder to obtain a mixed powder;

[0042] Step 4: Perform multi-mode pressing on the mixed powder to obtain multiple AgSnO 2 In 2 O 3Bi 2 O 3 Green body;

[0043] Step Five: Continuously sinter the AgSnO 2 In 2 O 3 Bi 2 O 3 green body to obtain a sintered green body;

[0044] Step Six: Perform secondary forming pressing on the sintered green body;

[0045] Step Seven: Heat-treat the green body after secondary forming pressing to obtain AgSnO 2 In 2 O 3 Bi 2 O 3 electrical contact material.

[0046] In the embodiments of the present invention, through multi-element oxide composite strengthening and adding trace elements (such as additive one), and combining processes such as secondary pressing, situations such as material segregation and weak bonding between the reinforcing phase and the matrix can be improved, and the interfacial bonding strength, material density, arc erosion resistance and other properties of the material can be improved; through processes such as multi-mode pressing and re-pressing, the density of the electrical contact material is greatly increased, and the arc erosion resistance of the material is further improved.

[0047] To obtain the two alloy intermediate powders of AgSnIn and AgSnBi, in some embodiments, in Step One, silver, tin, indium and additive two are used as raw materials, and atomization powder making is carried out by any one of water atomization, gas atomization, supersonic gas atomization, rotating electrode atomization, ultrasonic atomization and plasma atomization, and then sieved through 100-400 meshes to obtain AgSnIn alloy powder. By weight, the element ratio is: Ag:Sn:In = (40-70):(20-40):(10-20). Using silver, tin, bismuth and additive three as raw materials, atomization powder making is carried out by any one of water atomization, gas atomization, supersonic gas atomization, rotating electrode atomization, ultrasonic atomization and plasma atomization, and then sieved through 100-400 meshes to obtain AgSnBi alloy powder. By weight, the element ratio is: Ag:Sn:Bi = (52-76):(20-40):(4-8).

[0048] In the embodiments of the present invention, by selecting the above atomization method, spherical, satellite-shaped or dendritic particle morphologies can be obtained; among them, spherical and satellite-shaped particles are generally obtained by gas atomization or plasma atomization methods, while dendritic particles are generally obtained by water atomization and other methods; with different morphologies, the properties such as the fluidity of the particles will be different, thus affecting the speed of particle dispersion during the powder mixing process. Therefore, the subsequent powder mixing time needs to consider the particle morphology to achieve more uniform powder mixing. It should be noted that particle agglomeration is not only related to the particle morphology, but also closely related to factors such as particle material and particle size, and needs to be considered comprehensively. By selecting the above sieve mesh number, intermediate powder with the required particle size can be obtained. Thus, the prepared alloy intermediate powder facilitates the dispersion of powder particles during the subsequent powder mixing process, and no agglomeration occurs between the powder particles.

[0049] In some preferred embodiments, additive two is any one or more of Cu, Zn, Ni, Fe, Te, and Ge; additive three is any one or more of Cu, Zn, Ni, Fe, Te, and Ge. The role of the additives is to regulate the comprehensive electrical or mechanical properties of the material. For example, the Te element can improve the anti-welding ability of the electrical contact material and reduce the arcing ability; Fe and Cu elements help to improve the interfacial wettability, etc., thereby improving the densification of the material and enhancing the mechanical properties such as the bonding strength; the Zn element can enable the material to maintain the anti-welding performance while maintaining the deformability and processability; the Ni element can refine the grains and improve the mechanical properties of the material.

[0050] In some embodiments, in step two, the oxidation temperature is 400°C to 700°C, the oxidation time is 1 to 12 hours, and the atmosphere is air or oxygen atmosphere. Through the oxidation step, complete oxidation of the intermediate powder can be achieved without residue of the alloy powder.

[0051] In some embodiments, in step three, additive one is at least one of W and rare earth elements to improve the wettability between the reinforcement phase and pure silver, or increase the dislocation density and pinning effect, thereby improving the bonding strength between the reinforcement phase and the silver matrix and improving the plasticity of the material, etc. By mass percentage, the mass percentages of each powder are as follows: AgSnO 2 In 2 O 3 powder 40% - 60%, AgSnO 2 Bi 2 O 3 powder 10% - 20%, additive one 0 - 2.5%, and the balance is silver. The above powder mixing ratio and parameters are set according to the actual product requirements, and thus composite contact materials such as AgMeO(10), AgMeO(12), and AgMeO(14) are obtained.

[0052] Exemplarily, in step three, the powder mixing rotation speed is 20 revolutions per minute to 200 revolutions per minute, and the powder mixing time is 1 hour to 20 hours. Through the powder mixing step, the dispersibility of the powder can be improved, ensuring that each powder is evenly mixed and there is no agglomeration.

[0053] In order to improve the bonding strength between the reinforcing phase and the silver matrix, in some embodiments, before step four, it further includes: wet ball milling the mixed powder. Specifically, the mixed powder and the liquid medium are placed together in a ball mill for wet ball milling.

[0054] Exemplarily, the ball-to-powder ratio is 1 to 20, the ball milling rotation speed is 100 revolutions per minute to 400 revolutions per minute, and the ball milling time is 2 hours to 30 hours. After wet ball milling, it is then dried.

[0055] Through the above high-energy ball milling treatment, a powder with a core-shell structure is formed, enabling the multi-component reinforcing phase to be fully and evenly mixed, which can improve the surface activity of the powder, thereby enhancing the interfacial bonding strength between the reinforcing phase and the silver matrix, and significantly improving the performance stability of the electrical contact material.

[0056] To achieve multi-mode pressing, the embodiment of the present invention adopts a forming die with multiple cavities, and its structure is as Figure 2 shown. The die includes an upper die 1 and a lower die 2. The upper surface of the lower die 2 is provided with multiple cavities 3, and the lower surface of the upper die 1 is provided with multiple pressing heads 4 that cooperate with the cavities 3. In some embodiments, the mixed powder is subjected to multi-mode pressing to obtain an AgSnO 2 In 2 O 3 Bi 2 O 3 green body, including: first laying silver powder at the bottom of each cavity of a forming die with multiple cavities as Figure 2 shown, then feeding the mixed powder into each cavity in the forming die, and subsequently performing in-die pressing to form multiple AgSnO 2 In 2 O 3 Bi 2 O 3 green bodies. Among them, the pressing pressure is 300 MPa to 500 MPa, and the pressure holding time is 0.1 second to 60 seconds, thereby forming a dense and cornerless material green body. The pure silver powder laid in this step is not part of the electrical contact material component, but serves as a welding layer. The thickness ratio of the laid pure silver powder to the working layer of the AgSnO 2 In 2 O 3 Bi 2 O 3 electrical contact material working layer is (0.1 to 0.2):(0.8 to 0.9). Thus, the working layer material of the electrical contact (AgSnO 2 In2 O 3 Bi 2 O 3 Material) can be firmly connected to the support (such as copper).

[0057] In step 5, AgSnO 2 In 2 O 3 Bi 2 O 3 The green body is placed in a continuous sintering furnace for sintering. In some embodiments, the sintering temperature is 600° C. to 900° C., the sintering time is 1 hour to 10 hours, and the sintering atmosphere is any one of air, nitrogen and inert gas.

[0058] Through the above sintering process, a neck connection is formed between the powders, that is, a bridge is formed at the contact point between the two particles to connect the two particles. Due to the formation of the neck connection, the pores between the particles are significantly reduced, thereby improving the density of the material. In addition, after the neck connection is formed between the powder particles, it is equivalent to forming a conductive network of the material, increasing the movement path of electrons, thereby improving the conductivity.

[0059] In some embodiments, in step six, the secondary molding pressing pressure is 600 MPa to 800 MPa, and the holding time is 0.1 second to 60 seconds.

[0060] AgSnO is prepared by extrusion method in the prior art. 2 The material needs to remove the head and tail of the material after extrusion, the material utilization rate is low, and the extrusion pressure does not exceed 200MPa. When the extrusion ratio exceeds 30, the wire is prone to cracks and other defects. Therefore, the density of the material after extrusion is limited; conventional AgSnO 2 Pre-oxidation process, although the dense electrical contact material is obtained by re-pressing, but after the switch is disconnected many times, SnO is easy to appear on the surface of the material. 2 Segregation.

[0061] Compared with the extrusion method in the prior art, the above embodiment of the present invention uses multi-mode pressing and continuous sintering, which does not require the removal of the head and tail of the material, has a simple processing method, a high material utilization rate, and can process multiple blanks at a time, which significantly improves the production rate and yield rate of the electrical contact material, and is easy to mass produce. Moreover, the re-pressing pressure in the embodiment of the present invention far exceeds the conventional extrusion method, so after two pressings, the density of the material obtained in the above embodiment of the present invention is greatly improved, and the material is more resistant to arc ablation.

[0062] In some embodiments, in step seven, the heat treatment temperature is 300° C. to 550° C., and the heat treatment time is 0.5 to 6 hours. Through the heat treatment step, the pores of the material blank are further reduced, and the internal stress of the blank is released.

[0063] In order to improve the quality of the finished electric contact material, in some embodiments, after the green body after the secondary pressing is heat treated, it is cleaned to obtain an electric contact material with a clean and pollution-free surface.

[0064] The above embodiment of the present invention provides a method for preparing silver tin oxide electrical contact material with high efficiency and multi-mode continuous production, using SnO 2 、In 2 O 3 、Bi 2 O 3 The material has SnO composite reinforcement. 2 Environmentally friendly and non-toxic, with excellent resistance to material transfer under DC load, and In 2 O 3 The wettability improvement effect of Bi 2 O 3 The effect of improving the resistance to fusion welding is achieved; moreover, through the methods of multi-oxide mixing, powder mixing, high-energy ball milling and secondary pressing, the multi-component reinforcement phase is fully mixed and uniformly mixed, and at the same time, a layer of pure silver is coated on the surface of the reinforcement phase. In this way, the conventional mechanical powder mixing method easily leads to the segregation of the interface of the multi-component oxide composite reinforcement, the uneven distribution of the reinforcement phase, and the weak bonding between the reinforcement phase and the matrix. The segregation of the reinforcement phase and the uniformity of the reinforcement phase distribution are improved, and the AgSnO 2 In 2 O 3 Bi 2 O 3 The interface bonding strength, material density and arc erosion resistance of the electrical contact material are improved, thereby improving the electrical performance and service life of the product. In addition, the above embodiment of the present invention is formed by multi-mode continuous pressing, and multiple blanks can be pressed and formed at the same time, which effectively improves the production efficiency of the electrical contact material, the processing method is simple, and the yield rate is high.

[0065] Ag / SnO provided by the prior art (such as patent CN101964260A) 2 Electrical contact materials, also containing Bi 2 O 3 、In 2 O 3 SnO 2 These components are different from the prior art. The multi-component oxides in the above embodiment of the present invention are generated in situ, that is, the AgSnIn alloy powder is in situ oxidized into AgSnO 2 In 2O 3 The AgSnBi alloy powder is in-situ oxidized to AgSnO 2 Bi 2 O 3 so that the interior of the oxide-reinforced phase powder also contains Ag, thereby improving the wettability of the reinforced phase, further enhancing the interfacial bonding strength between the reinforced phase and the silver matrix, and improving the density and arc erosion resistance of the material. Additionally, since the reinforced phase contains silver inside, that is, a silver network structure is formed inside the reinforced phase, which is beneficial for electrons to flow through the interior of the reinforced phase, thereby improving the electrical conductivity of the material.

[0066] In patent CN101964260A, the SnInBi alloy powder is oxidized to SnO 2 In 2 O 3 Bi 2 O 3 as the reinforced phase. This reinforced phase does not contain silver inside and no silver network structure is formed, and this reinforced phase is essentially a ceramic material. When mixed with silver powder subsequently, its interfacial wettability is far inferior to that of the powder in the embodiment of the present invention. Correspondingly, the strength, density, electrical conductivity, and arc erosion resistance of its electrical contact material are also inferior to those of the electrical contact material provided in the embodiment of the present invention.

[0067] The solutions of the present application will be explained below in combination with specific examples and comparative examples. Those skilled in the art can understand that the following examples are only used to illustrate the present application and should not be regarded as limiting the scope of the present application. For those not specified in the examples in terms of specific techniques or conditions, they shall be carried out according to the techniques or conditions described in the literature in the art or according to the product specifications. For the reagents or instruments not specified in terms of the manufacturer, they are all conventional products that can be obtained through commercial channels.

[0068] Example

[0069] This example provides a preparation method for an efficient and multi-mode continuous production of AgSnO 2 In 2 O 3 Bi 2 O 3 electrical contact material, including the following steps:

[0070] S1: Using Ag, Sn, In, and additive Cu as raw materials, atomizing to produce powder by supersonic gas atomization, and sieving the powder through a 300-mesh sieve to obtain AgSnIn alloy powder; simultaneously, using Ag, Sn, Bi, and additive Te as raw materials, atomizing to produce powder by plasma atomization, and sieving the powder through a 300-mesh sieve to obtain AgSnBi alloy powder.

[0071] S2: Respectively place the AgSnIn alloy powder and the AgSnBi alloy powder in an oxidation furnace at 600 °C, introduce high-pressure oxygen, and oxidize for 2 hours to obtain AgSnO 2 In 2 O 3 and AgSnO 2 Bi 2 O 3 powders.

[0072] S3: Place the AgSnO 2 In 2 O 3 powder, the AgSnO 2 Bi 2 O 3 powder, the additive W, and the Ag powder in a powder mixer, and mix the powder for 3 hours at a rotation speed of 180 revolutions per minute to obtain a mixed powder.

[0073] S4: Place the mixed powder and absolute ethanol together in a horizontal ball mill for wet ball milling; the ball milling process parameters are: the ball-to-material ratio is 10, the ball milling rotation speed is 300 revolutions per minute, and the ball milling time is 4 hours.

[0074] S5: Use the Figure 2 shown forming die with multiple cavities to simultaneously feed the ball-milled mixed powder into each cavity in the forming die, and then perform in-mold pressing, where the pressing pressure is 500 MPa and the pressure holding time is 20 seconds to obtain multiple AgSnO 2 In 2 O 3 Bi 2 O 3 green bodies.

[0075] S6: Place the AgSnO 2 In 2 O 3 Bi 2 O 3 green bodies on a tray and place them in a continuous sintering furnace, introduce nitrogen, and perform sintering treatment, where the sintering temperature is 880 °C and the sintering time is 4 hours to obtain sintered green bodies.

[0076] S7: Perform secondary forming pressing on the sintered green bodies, where the pressure of the secondary forming pressing is 800 MPa and the pressure holding time is 30 seconds.

[0077] S8: Heat-treat the billet after secondary pressing at a temperature of 550 °C for 2 hours, and then wash it to obtain the AgSnO 2 In 2 O 3 Bi 2 O 3 finished product of the electrical contact material.

[0078] Comparative Example

[0079] Comparative Example: AgSnO was prepared by conventional extrusion method. 2 Electrical contact materials.

[0080] The AgSnO prepared in the embodiment of the present invention 2 In 2 O 3 Bi 2 O 3 The finished electrical contact material was compared and evaluated with the electrical contact material prepared by conventional extrusion in the comparative example in terms of hardness, electrical life and yield rate. The detailed results are shown in Table 1 below.

[0081] Table 1 Characterization results of electrical contact materials in examples and comparative examples

[0082] Hardness Electrical life test Yield rate Example 117HV 16,000 times 90% Comparative example 102HV 10,800 times 48%

[0083] As can be seen from Table 1, the silver tin oxide electrical contact material for low-voltage electrical appliances with denser material, better arc erosion resistance and higher yield rate is prepared by the method provided in the embodiment of the present invention. In addition, the above-mentioned hardness and arc wear and ablation resistance reflect from the side that the electrical contact material in the embodiment of the present invention has a higher interface bonding strength.

[0084] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various modifications or variations within the scope of the claims, which does not affect the essence of the present invention. The above preferred features can be used in any combination without conflicting with each other.

Claims

1. A method for preparing an AgSnO2In2O3Bi2O3 electrical contact material, characterized in that: include: Provide AgSnIn alloy powder and AgSnBi alloy powder; The AgSnIn alloy powder is oxidized to form AgSnO2In2O3 powder; the AgSnBi alloy powder is oxidized to form AgSnO2Bi2O3 powder; Mixing the AgSnO2In2O3 powder, the AgSnO2Bi2O3 powder, the additive 1 and the silver powder to obtain a mixed powder; The mixed powder is subjected to multi-mode pressing to obtain a AgSnO2In2O3Bi2O3 green body; Continuously sintering the AgSnO2In2O3Bi2O3 green body to obtain a sintered green body; Performing secondary molding and pressing on the sintered green body; The green body after secondary molding and pressing is heat treated to obtain AgSnO2In2O3Bi2O3 electrical contact material.

2. The method for preparing the AgSnO2In2O3Bi2O3 electrical contact material according to claim 1, characterized in that: The provision of AgSnIn alloy powder and AgSnBi alloy powder comprises: Using silver, tin, indium and additive 2 as raw materials, atomizing and powdering is performed by any one of water atomization, gas atomization, supersonic air flow atomization, rotary electrode atomization, ultrasonic atomization and plasma atomization, and sieving through 100-400 meshes to obtain AgSnIn alloy powder; Silver, tin, bismuth and additives are used as raw materials, and powder is atomized and powdered by any one of water atomization, gas atomization, supersonic air flow atomization, rotary electrode atomization, ultrasonic atomization and plasma atomization, and sieved with 100-400 meshes to obtain AgSnBi alloy powder.

3. The method for preparing the AgSnO2In2O3Bi2O3 electrical contact material according to claim 2, characterized in that: The second additive is any one or more of Cu, Zn, Ni, Fe, Te and Ge; the third additive is any one or more of Cu, Zn, Ni, Fe, Te and Ge.

4. The method for preparing the AgSnO2In2O3Bi2O3 electrical contact material according to claim 1, characterized in that: In the step of oxidizing the AgSnIn alloy powder and / or oxidizing the AgSnBi alloy powder, the oxidation temperature is 400° C. to 700° C., the oxidation time is 1 to 12 hours, and the atmosphere is air or oxygen atmosphere.

5. The method for preparing the AgSnO2In2O3Bi2O3 electrical contact material according to claim 1, characterized in that: The AgSnO2In2O3 powder, the AgSnO2Bi2O3 powder, additive one and silver powder are mixed to obtain a mixed powder, wherein the additive one is at least one of W and a rare earth element.

6. The method for preparing the AgSnO2In2O3Bi2O3 electrical contact material according to claim 1, characterized in that: Before the mixed powder is subjected to multi-mode pressing, the mixed powder is wet-milled.

7. The method for preparing the AgSnO2In2O3Bi2O3 electrical contact material according to claim 1, characterized in that: The method of subjecting the mixed powder to multi-mold pressing to obtain AgSnO2In2O3Bi2O3 green bodies comprises: pre-laying silver powder on the bottom of each cavity of a forming mold having multiple cavities, then feeding the mixed powder into each cavity in the forming mold, and then performing in-mold pressing to obtain multiple AgSnO2In2O3Bi2O3 green bodies.

8. The method for preparing the AgSnO2In2O3Bi2O3 electrical contact material according to claim 1, characterized in that: The AgSnO2In2O3Bi2O3 green body is continuously sintered to obtain a sintered green body, wherein: the sintering temperature is 600°C to 900°C, the sintering time is 1 hour to 10 hours, and the sintering atmosphere is any one of air, nitrogen and inert gas.

9. The method for preparing the AgSnO2In2O3Bi2O3 electrical contact material according to claim 1, characterized in that: The sintered green body is subjected to secondary molding and pressing, wherein the pressure of the secondary molding and pressing is 600 MPa to 800 MPa, and the holding time is 0.1 second to 60 seconds.

10. The method for preparing the AgSnO2In2O3Bi2O3 electrical contact material according to claim 1, characterized in that: The green body after secondary molding and pressing is heat treated to obtain AgSnO2In2O3Bi2O3 electrical contact material, wherein: the heat treatment temperature is 300°C to 550°C, and the heat treatment time is 0.5 hour to 6 hours.

Citation Information

Patent Citations

  • Ag / SnO2 electrical contact material and preparation method thereof

    CN101964260A

  • Method for preparing silver tin oxide electrical contact

    CN102328086A

  • Silver tin oxide and indium oxide electric contact material and preparation method thereof

    CN107794389A

  • Silver tin oxide indium oxide electric contact composite material and preparation method thereof

    CN114360948A